Non-Dissecting Distal Aortic and Peripheral Arterial Aneurysms in Patients With Marfan Syndrome - Pellenc, Quentin; Boitet, Auréline; Roussel, Arnaud; Milleron, Olivier; Mordant, Pierre; Senemaud, Jean; Cerceau, Pierre; Jondeau, Guillaume; Castier, Yves (Frontiers in Cardiovascular Medicine, 2022)
Background In Marfan syndrome (MFS), an aortic or peripheral arterial dilatation is usually the consequence of aortic dissection. Non-dissecting distal aortic and peripheral aneurysms (DAPA) are barely described. We sought to determine the incidence and prognostic impact of non-dissecting DAPA, requiring a surgical repair in a large population of patients with MFS. Methods The patients referred to the French MFS reference center were included in a prospective database, and the patients treated for a non-dissecting DAPA between 2013 and 2020 were retrospectively reviewed. The first-line therapy was open surgery. The patients unfit for open repair or experiencing life-threatening complications underwent endovascular repair. Results Among 1,575 patients with MFS, 19 (1.2%) were operated for 25 non-dissecting DAPA. The mean age was 42.4 ± 11.5 years. Non-dissecting DAPA involved the subclavian or axillary artery (n = 12), the descending or thoracoabdominal aorta (n = 6), the abdominal aorta andiliac arteries (n = 6), and the popliteal artery (n = 1). Open and endovascular repairs were performed in 22 and three cases, respectively. After a median follow-up of 54.2 months, no local recurrence was noticed and no secondary procedure was performed. Eight patients presented a new aortic event, including two aortic dissections and seven new aortic surgeries. Compared to the overall MFS population, the non-dissecting DAPA group presented a significantly higher risk of an aortic event (100 vs. 28%, p < 0.0001), a higher risk of aortic dissection (53 vs. 8%, p < 0.0001), and a higher rate of pejorative genetic mutations (68 vs. 40%, p = 0.011). Conclusion Among the patients with MFS, the diagnosis of non-dissecting DAPA is infrequent but is associated with a significant adverse outcome, thus, advocating for a specific follow-up.